Effect of short-term use of oral contraceptive pills on intraocular pressure - Malik, Tayyaba Gul; Nadeem, Hina; Ayesha, Eiman; Alam, Rabail (Pakistan Journal of Ophthalmology, 2020)
Objective: To study the effect of short-term use of oral contraceptive pills on intra-ocular pressures of women of childbearing age. Methods: It was a comparative observational study, conducted at Arif memorial teaching hospital and Allied hospital Faisalabad for a period of six months. Hundred female subjects were divided into two groups of 50 each. Group A, included females, who had been taking oral contraceptive pills (OCP) for more than 6 months and less than 36 months. Group B, included 50 age-matched controls, who had never used OCP. Ophthalmic and systemic history was taken. Careful Slit lamp examination was performed and intraocular pressures (IOP) were measured using Goldman Applanation tonometer. Fundus examination was done to rule out any posterior segment disease. After collection of data, we analyzed and compared the intra ocular pressures between the two groups by using ANOVA in SPSS version 21. Results: Average duration of using OCP was 14.9 months. There was no significant difference of Cup to Disc ratios between the two groups (p= 0.109). However, significant difference was noted between the IOP of OCP group and controls. (p=0.000). Conclusion: OCP significantly increase IOP even when used for short time period.